Bosutinib Therapy Ameliorates Lung Inflammation and Fibrosis in Experimental Silicosis - Carneiro, Priscila J.; Clevelario, Amanda L.; Padilha, Gisele A.; Silva, Johnatas D.; Kitoko, Jamil Z.; Olsen, Priscilla C.; Capelozzi, Vera L.; Rocco, Patricia R. M.; Cruz, Fernanda F. (Frontiers in Physiology, 2017)
Silicosis is an occupational lung disease for which no effective therapy exists. We hypothesized that bosutinib, a tyrosine kinase inhibitor, might ameliorate inflammatory responses, attenuate pulmonary fibrosis, and thus improve lung function in experimental silicosis. For this purpose, we investigated the potential efficacy of bosutinib in the treatment of experimental silicosis induced in C57BL/6 mice by intratracheal administration of silica particles. After 15 days, once disease was established, animals were randomly assigned to receive DMSO or bosutinib (1 mg/kg/dose in 0.1 mL 1% DMSO) by oral gavage, twice daily for 14 days. On day 30, lung mechanics and morphometry, total and differential cell count in alveolar septa and granuloma, levels of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, IL-4, transforming growth factor (TGF)-β, and vascular endothelial growth factor in lung homogenate, M1 and M2 macrophages, total leukocytes and T cells in BALF, lymph nodes, and thymus, and collagen fiber content in alveolar septa and granuloma were analyzed. In a separate in vitro experiment, RAW264.7 macrophages were exposed to silica particles in the presence or absence of bosutinib. After 24 hours, gene expressions of arginase-1, IL-10, IL-12, inducible nitric oxide synthase (iNOS), metalloproteinase (MMP)-9, tissue inhibitor of metalloproteinase (TIMP)-1, and caspase-3 were evaluated. In vivo, in silicotic animals, bosutinib, compared to DMSO, decreased: 1) fraction area of collapsed alveoli, 2) size and number of granulomas, and mononuclear cell granuloma infiltration; 3) IL-1β, TNF-α, IFN-γ, and TGF-β levels in lung homogenates, 4) collagen fiber content in lung parenchyma, and 5) viscoelastic pressure and static lung elastance. Bosutinib also reduced M1 cell counts while increasing M2 macrophage population in both lung parenchyma and granulomas. Total leukocyte, regulatory T, CD4+, and CD8+ cell counts in the lung-draining lymph nodes also decreased with bosutinib therapy without affecting thymus cellularity. In vitro, bosutinib led to a decrease in IL-12 and iNOS and increase in IL-10, arginase-1, MMP-9, and TIMP-1. In conclusion, in the current model of silicosis, bosutinib therapy yielded beneficial effects on lung inflammation and remodeling, therefore resulting in lung mechanics improvement. Bosutinib may hold promise for silicosis; however, further studies are required.